2015
DOI: 10.3174/ajnr.a4462
|View full text |Cite
|
Sign up to set email alerts
|

Endolymphatic Hydrops Reversal following Acetazolamide Therapy: Demonstration with Delayed Intravenous Contrast-Enhanced 3D-FLAIR MRI

Abstract: SUMMARY: Endolymphatic hydrops, the primary pathologic alteration in Menière disease, can be visualized by using delayed intravenous contrast-enhanced 3D-FLAIR MR imaging. It is not known whether MR imaging-demonstrable changes of hydrops fluctuate with disease activity or are fixed. We describe the results of baseline and posttreatment MR imaging studies in a group of subjects with Menière disease with hydrops who were treated with acetazolamide. Seven subjects with untreated Menière disease with MR imaging e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 12 publications
1
34
0
Order By: Relevance
“…Intravenous gadolinium enhanced magnetic resonance imaging (MRI) can be used to visualize and quantify endolymphatic hydrops 22, 35 . Gadolinium, an agent used in magnetic resonance imaging (MRI), is taken up into the perilymph, presumably via perfusion through the BLB, specifically through the blood-perilymphatic barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous gadolinium enhanced magnetic resonance imaging (MRI) can be used to visualize and quantify endolymphatic hydrops 22, 35 . Gadolinium, an agent used in magnetic resonance imaging (MRI), is taken up into the perilymph, presumably via perfusion through the BLB, specifically through the blood-perilymphatic barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, our understanding of cochlear disorders was based on histologic or molecular findings in postmortem and animal studies. With advances in imaging techniques, however, magnetic resonance imaging (MRI) is now being used in the study of endolymphatic hydrops (EH) and SSNHL . Though the mechanism for SSNHL associated with PDE5 inhibitor use remains unknown, it has been recently reported that inhibition of phosphodiesterase in mice results in EH .…”
Section: Introductionmentioning
confidence: 99%
“…Milon and colleagues have suggested the possibility of utilizing estrogen signaling pathway effectors for hearing protection (Milon et al, 2018). In the Bmyc regulon, both metformin and acetazolamide have been associated with attenuation of hearing loss in certain settings (H. C. Chen, Chung, Lu, & Chien, 2019;Muri, Le, Zemp, Grandgirard, & Leib, 2019;Sepahdari, Vorasubin, Ishiyama, & Ishiyama, 2016;Wester, Ishiyama, Karnezis, & Ishiyama, 2018). Metformin, which inhibits Ndufb2, may reduce the incidence of sudden sensorineural hearing loss amongst diabetic patients (H. C. Chen et al, 2019;Muri et al, 2019).…”
Section: Pharos Analysis Identifies Druggable Gene Targets In Cell Tymentioning
confidence: 99%